Design and Prototyping of Solar Operated Fertilizer Sprayer. - Nduhura, Whycliffee (Kabale University, 2023)
A sprayer is a mechanical device used to spray the liquid chemicals like herbicides, pesticides, fungicides and fertilizers to the crops in order to control pests and diseases on crops to maximize production. Sprayers are of many different kinds which include knapsack sprayers, motorized sprayers, tractor drawn sprayers, etc. The most commonly used type by the Ugandan farmers are the knapsack sprayers which have to be carried at the back requiring a lot of physical effort to actuate the lever by one hand at a frequency of 15 to 20 strokes per minute because they are cheap in terms of capital cost. The main drawback with these sprayers is that they cannot be used for long working hours due to human drudgery and cause fatigue to the person spraying due to back pains and muscular problems making the entire operation tedious and time consuming and they also have low pressure. Motorized sprayers have high pressure but with high investment cost and maintenance cost. Due to the above shortcomings of the commonly used sprayers, the need for another means which provide output in between the knapsack sprayers and the motorized sprayers calls for the invention of solar powered/operated sprayers. These can have between low to high pressure depending on the capacity of the pump. These sprayers also cost moderately and have low maintenance costs. For this project, the emphasis was put on the design, construction and testing for the performance of a solar operated fertilizer sprayer using low power pump and solar panel. The main components of the solar operated fertilizer sprayer include; wheels, nozzles, tank, pump, tank, and frame. The materials of construction were selected basing on strength, availability and durability. During the design process, the required solar panel, pump, battery and angle of solar panel inclination were obtained based on the required output of 3litres/min of the chemical. The system was tested under varying conditions of insolation strengths and an angle of inclination of the solar panel. It was observed that the rate of discharge is affected by the strength of solar insolation and angle with the appropriate angle being 45degrees. Implementation of this project will help in saving costs spent on fuel purchase and reduce the spraying time due to moderate pressure and improve on the yield of specified crops.